2004
DOI: 10.1089/neu.2004.21.1355
|View full text |Cite
|
Sign up to set email alerts
|

A Global Perspective on Spinal Cord Injury Epidemiology

Abstract: Spinal cord injury (SCI) is a devastating condition often affecting young and healthy individuals around the world. This debilitating condition not only creates enormous physical and emotional cost to individuals but also is a significant financial burden to society at large. This review was undertaken to understand the global impact of SCI on society. We also attempted to summarize the worldwide demographics and preventative strategies for SCI in varying economic and climatic environments and to evaluate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
287
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 409 publications
(312 citation statements)
references
References 42 publications
16
287
1
8
Order By: Relevance
“…The estimated annual incidence reported in this study (more than 26 persons per million population) is relatively high as compared to the reported globally and in low income countries (23 and 25.5 persons per million population) respectively [5,12,18]. However there are other country and regional–specific studies that have reported higher annual incidences such as in Cape Town – South Africa and the United States which reports 75 and 54 persons per million population respectively [8,19].…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The estimated annual incidence reported in this study (more than 26 persons per million population) is relatively high as compared to the reported globally and in low income countries (23 and 25.5 persons per million population) respectively [5,12,18]. However there are other country and regional–specific studies that have reported higher annual incidences such as in Cape Town – South Africa and the United States which reports 75 and 54 persons per million population respectively [8,19].…”
Section: Discussionmentioning
confidence: 68%
“…Trauma to the spinal cord may result from a road traffic accident (RTA), fall, assault and recreational or occupational accident [1,5]. The World Health Organization informs that up to 90% of all spinal cord lesions are due to trauma and that the leading cause globally is RTA [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations